A PROGNOSTIC CONTRIBUTION OF BIDIMENSIONAL LEFT ATRIAL STRAIN IN PATIENTS WITH ASYMPTOMATIC MITRAL STENOSIS: ABOUT A TUNISIAN POPULATION - YAAKOUBI, WAEL (Medicinski časopis, 2023)
Background: The two-dimensional strain is an objective echocardiographic technique allowing the quantification of myocardial deformation. The aim of this study was to specify prognostic contribution of left atrial strain in patients with asymptomatic mitral stenosis. Methods: We included consecutive patients followed for severe or moderately severe rheumatic Mitral Stenosis (MS), asymptomatic, during the period from January 2015 to June 2020 in military hospital of Tunis. The patients followed were divided into two groups according to one criterion of judgment composed of: Cardiac mortality, The occurrence of hospitalization for cardiac reasons, The occurrence of atrial fibrillation (AF), The occurrence of a thromboembolic event and the need for cardiac surgery or mitral valvuloplasty. Results: Initially eighteen patients were selected but only 53 were followed and then divided into two groups: 30 patients had at least one event and 23 patients had no event according to the occurrence of the major endpoint of the study. In a univariate study and for conventional echocardiographic parameters, we determined that if Left Atrium Area (LAA) is larger than 30 cm2 and left atrium volume (LAV) more than 100ml/m2, the risk of occurrence of an event increased respectively significantly (LAA: 69% vs 10%; p = 0.01; OR = 6.6; 95% CI [1.5-28]) and (LAV: 71,4% vs 39%; p = 0.002; OR = 4; 95% CI [1,1-13]). The same for left atrium deformation parameters, both Peak Atrial Longitudinal Strain (PALS) <25% and Peak Atrial Contraction Strain (PACS) <10 % were predictive of events in univariate study with these following respective odds ratios (ORs) (PALS: 83% vs 30.4%; p = 0.0001; OR = 11.4; 95% CI [3-42]), and (PACS: 90% vs 47%; p = 0.001; OR = 9.8; 95% CI [2.3-41]).In a multivariate study, the only independent parameter of the occurrence of an event was PACS <10% (p = 0.013; OR = 44; 95% CI [2.19-80]). Conclusion: PACS have prognostic value in asymptomatic MS as it predicts occurring of pathologic events in the following of patients with asymptomatic